2022
DOI: 10.1038/s41598-022-22404-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of complement C3 inhibitor pegcetacoplan with reduced photoreceptor degeneration beyond areas of geographic atrophy

Abstract: Preservation of photoreceptors beyond areas of retinal pigment epithelium atrophy is a critical treatment goal in eyes with geographic atrophy (GA) to prevent vision loss. Thus, we assessed the association of treatment with the complement C3 inhibitor pegcetacoplan with optical coherence tomography (OCT)-based photoreceptor laminae thicknesses in this post hoc analysis of the FILLY trial (NCT02503332). Retinal layers in OCT were segmented using a deep-learning-based pipeline and extracted along evenly spaced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Interestingly, independent groups demonstrated that AI‐based OCT quantification of retinal layers can reveal progressive photoreceptor degeneration outside areas of GA (Figure 2) (Pfau, Möller, Künzel, et al., 2020; Pfau, von der Emde, de Sisternes, et al., 2020; Pfau, von der Emde, Dysli, et al., 2020; Reiter et al., 2020). Even therapeutic effects at the level of photoreceptors outside of GA areas could be demonstrated by two independent groups for pegcetacoplan (Pfau et al., 2022; Riedl et al., 2022).…”
Section: Artificial Intelligence In Geographic Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, independent groups demonstrated that AI‐based OCT quantification of retinal layers can reveal progressive photoreceptor degeneration outside areas of GA (Figure 2) (Pfau, Möller, Künzel, et al., 2020; Pfau, von der Emde, de Sisternes, et al., 2020; Pfau, von der Emde, Dysli, et al., 2020; Reiter et al., 2020). Even therapeutic effects at the level of photoreceptors outside of GA areas could be demonstrated by two independent groups for pegcetacoplan (Pfau et al., 2022; Riedl et al., 2022).…”
Section: Artificial Intelligence In Geographic Atrophymentioning
confidence: 99%
“…However, many of the more refined analyses (e.g. degree of retina‐wide photoreceptor degeneration) (Pfau et al., 2022; Pfau, Möller, Künzel, et al., 2020; Pfau, von der Emde, de Sisternes, et al., 2020; Pfau, von der Emde, Dysli, et al., 2020; Riedl et al., 2022), necessitate algorithms that are currently only available in a reading centre setting. Furthermore, assessment of larger GA lesions may be impaired by the limited OCT scan field, at least with some of the current OCT devices.…”
Section: Established Imaging Techniquesmentioning
confidence: 99%
“…Pegcetacoplan demonstrated its efficacy in preserving photoreceptors beyond the regions of retinal pigment epithelium (RPE) atrophy, a pivotal goal in managing eyes with geographic atrophy (GA) to mitigate vision deterioration. Post hoc analysis, on both monthly and bi‐monthly regimens, exhibited a pronounced thickness in the outer nuclear layer (ONL) relative to the control group as well as a thicker photoreceptor inner segment layer was observed in pegcetacoplan‐treated eyes by Month 12 (Pfau et al., 2022).…”
Section: Completed Trialsmentioning
confidence: 99%
“…Therefore, additional therapeutic approaches are desirable. GA progression is typically assessed by manual reading center grading of fundus autofluorescence (FAF) images, although automated segmentation of FAF and optical coherence tomography (OCT) images has been described …”
Section: Introductionmentioning
confidence: 99%
“…GA progression is typically assessed by manual reading center grading of fundus autofluorescence (FAF) images, although automated segmentation of FAF and optical coherence tomography (OCT) images has been described. 6,7 The innate immune system is centrally involved in GA pathogenesis. [8][9][10][11] AMD is characterized by the accumulation of activated cells of the innate immune system in the subretinal space, at the hallmark lesions of large drusen and GA. 8,11,12 In GA, they are found in both atrophic areas and surrounding transition zones.…”
mentioning
confidence: 99%